Developing thinking and understanding in young children : an introduction for students - Robson, Sue (London ; New York, NY : Routledge, Taylor & Francis Group, 2020)
"The third edition of this essential book presents a comprehensive and accessible overview of contemporary theory and research about young children's developing thinking and understanding. Sue Robson's detailed exploration of the ideas and theories is enlivened by transcripts of children's activities and conversations taken from practice and contemporary research, helping readers to make links between theory, research and practice. This new edition brings together up-to-date research into neuroscience and digital learning, combining theory with discussions for best practice. Each chapter also includes ideas for further reading and suggested activities. Key chapters explore: Theories of cognitive development The social, emotional and cultural contexts of children's thinking Developments in brain science and young children The central roles of play and language in young children's developing thinking Children's conceptual development; visual thinking and thinking in music This book is crucial reading for all those interested in how young children develop through their thoughts and actions, including students of Early Years studies; teachers and early years practitioners"--
How can we think about young children's thinking? -- Theories of cognitive development: learning to think and thinking to learn -- The social, cultural and emotional contexts of thinking and understanding -- The brain and the body : neuroscience and embodied cognition -- Knowing about the mind : executive function, theory of mind, self-regulation and metacognition -- Observing, describing and documenting children's thinking and understanding -- Language, communication and thought -- Knowing about the world : the development of children's concepts -- Young children's visual thinking -- Young children's thinking in music -- Approaches to developing young children's thinking and understanding
Includes bibliographical references and index.
PBK.
Description based on print version record and CIP data provided by publisher.
Keywords: Early childhood education; Thought and thinking -- Study and teaching (Early childhood); Cognition in children